2012
DOI: 10.1128/jvi.01352-12
|View full text |Cite
|
Sign up to set email alerts
|

Sequences in Glycoprotein gp41, the CD4 Binding Site, and the V2 Domain Regulate Sensitivity and Resistance of HIV-1 to Broadly Neutralizing Antibodies

Abstract: The swarm of quasispecies that evolves in each HIV-1-infected individual represents a source of closely related Env protein variants that can be used to explore various aspects of HIV-1 biology. In this study, we made use of these variants to identify mutations that confer sensitivity and resistance to the broadly neutralizing antibodies found in the sera of selected HIV-1-infected individuals. For these studies, libraries of Env proteins were cloned from infected subjects and screened for infectivity and neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 72 publications
3
26
0
Order By: Relevance
“…Glycans on HIV-1 envelope proteins have been shown or postulated to play an important and multifaceted role in viral replication, including structural integrity of the virus, coreceptor usage, evasion of host immune responses, and as targets for bNAbs (21,23,57,70,76). Here, we report a conserved role for the N-linked glycan at amino acid position 197 (N7) in modulating the antigenicity of the CD4bs and epitopes in the V3 loop, a major determinant for coreceptor usage.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Glycans on HIV-1 envelope proteins have been shown or postulated to play an important and multifaceted role in viral replication, including structural integrity of the virus, coreceptor usage, evasion of host immune responses, and as targets for bNAbs (21,23,57,70,76). Here, we report a conserved role for the N-linked glycan at amino acid position 197 (N7) in modulating the antigenicity of the CD4bs and epitopes in the V3 loop, a major determinant for coreceptor usage.…”
Section: Discussionmentioning
confidence: 89%
“…Because glycans on HIV-1 play an important role in the structure and function of Env (63,83,84) and because multiple studies have shown that carbohydrates modulate Env antigenicity (21,23,57,70,76,(85)(86)(87)(88)(89)(90), glycan modification may represent a rational approach for immunogen design. Although multiple studies have shown little or negative impact of glycan modifications on Env immunogenicity (91)(92)(93)(94)(95), we previously demonstrated that removal of specific glycans may enhance the ability of HIV Env to elicit neutralizing antibody responses (21).…”
Section: Discussionmentioning
confidence: 99%
“…D197, which results in loss of a PNGS located at the HIV Env trimer apex that determines neutralization sensitivity/resistance in several primary isolates (Kolchinsky et al, 2001b; Li et al, 2008; O’Rourke et al, 2012; Pantophlet et al, 2003; Rizzuto et al, 1998; Saphire et al, 2001), is a rare polymorphism that was detected in brain in some patients with HAD. Codon 200 was estimated to be under positive selection in both brain and lymphoid sequences from HAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…M434 mutated to I434 might have an effect on stabilizing the CD4-bound conformation of the Env (53-55). Thus, it is possible that particular C4 mutations, such as M434I, impact the exposure of the CD4 binding site epitope for neutralizing antibodies (22,48,51,52). In the present study, the M434I mutation showed enhanced neutralization sensitivity to anti-CD4bs, b12, and 0.5d NMAbs.…”
Section: Discussionmentioning
confidence: 46%
“…M434I, for instance, was observed in escape variants from the attachment inhibitor BMS-378806 and its derivatives (49,50). Furthermore, some C4 mutations in the Env region also occur in neutralizing antibody sensitive variants (48,51,52). These C4 mutations, including M434I, are located in close proximity to the CD4 binding area.…”
Section: Discussionmentioning
confidence: 99%